A brief introduction to contemporary electrokinetics. Issue 2 (3rd April 2021) - Żuk, Paweł Jan
Abstract : The first notion of ions comes from Michael Faraday, and since then, many successes in understanding their nature have been achieved. The motion of charged molecules is necessary to maintain the energy flux through all living organisms, constantly accompanying energy conversion and storage at the cellular level. The industry uses them alike: for energy and chemical processing. The motion of charged particles is also used for entertainment, e.g. pitching thrill in motorsports when kinetic energy recovery systems provide immediate access to power stored in supercapacitors during the most dynamic manoeuvres. However, after almost 200 years, there are still many open, technological, and fundamental questions. The reader will find a perspective on fundamental and vibrantly researched phenomena, including ion transport, and ideas essential to understanding them.